1998
DOI: 10.3109/03639049809085663
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Bioavailability of Griseofulvin by Its Complexation with β-Cyclodextrin

Abstract: Griseofulvin is a poorly soluble antifungal antibiotic drug, the solubility of which can be enhanced by complexation with beta-cyclodextrin. The inclusion complex was prepared by coprecipitation method in various molar ratios of 1:1, 2:1, 3:1, and 1:2 of the drug and beta-cyclodextrin, respectively. The inclusion complex was characterized and evaluated by UV-VIS spectral studies and FTIR. The in vitro drug release studies indicated that the 1:2 molar ratio complex form of the drug significantly increased the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…3,4) In the pharmaceutical field this complexation phenomenon has been extensively applied to enhance the solubility, dissolution rate, and bioavailability of sparingly soluble drugs in gastrointestinal fluids. [5][6][7][8][9][10] Because of the increasing interest in CDs and their inherent usefulness, several studies have been conducted to clarify the mechanism of complexation.…”
mentioning
confidence: 99%
“…3,4) In the pharmaceutical field this complexation phenomenon has been extensively applied to enhance the solubility, dissolution rate, and bioavailability of sparingly soluble drugs in gastrointestinal fluids. [5][6][7][8][9][10] Because of the increasing interest in CDs and their inherent usefulness, several studies have been conducted to clarify the mechanism of complexation.…”
mentioning
confidence: 99%
“…In the pharmaceutical field this phenomenon has been extensively applied to enhance the solubility, dissolution rate and bioavailability of slightly soluble drugs in gas-trointestinal fluids (Vila-Jato et al, 1988;Soliman et al, 1997;Ventura et al, 1997;Dhanaraju et al, 1998;O 8 zdemir and Ordu, 1998;Mura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[13]. Previous studies showed an increase in drug dissolution by complexation with cyclodextrin corresponded with increase oral bioavailability of griseofulvin and spironolactone; but not of naproxen and tolbutamide [14] [15] [16] [17]. In one another study it was reported that release of diclofenac sodium from matrix was inhibited by polymer chitosan via formation of ionic complex between diclofenac sodium and cationic polymer [18].…”
Section: Introductionmentioning
confidence: 99%